MRI findings of papillary cystadenocarcinoma of the submandibular gland - Koc, Mustafa; Yanilmaz, Muhammed; Yildirim, Hanefi; Gok, Uzeyir; Cobanoglu, Bengu (Turkish Soc Radiology, 2010)
Papillary cystadenocarcinoma is an extremely rare malignant tumor of the salivary glands. Major locations of this neoplasm are the parotid gland, sublingual gland, and minor salivary glands, while occurrence in the submandibular gland is extremely rare. Magnetic resonance imaging (MRI) findings Of this lesion have not been reported in the literature. Herein, we present a case of papillary cystadenocarcinoma arising from the right submandibular gland. MRI showed a 5-cm mass composed of solid and cystic components in the mildly enlarged gland. Pathologic evaluation revealed papillary cystadenocarcinoma.
Keywords: submandibular gland; cystadenocarcinoma, papillary; magnetic resonance imaging